Clinical evaluation of patterned dried plasma spot cards to support quantification of HIV viral load and reflexive genotyping - Giorgio Gianini Morbioli; Keith R. Baillargeon; Monalisa N. Kalimashe; Vibha Kana; Hloniphile Zwane; Cheri van der Walt; Allison J. Tierney; Andrea C. Mora; Mark Goosen; Rivashni Jagaroo; Jessica C. Brooks; Ewaldé Cutler; et al. (Proceedings of the National Academy of Sciences, 2025)
Quantifying viral load, a key indicator required to achieve control and elimination of the HIV epidemic, requires cell-free plasma or serum to ensure measurements are not biased by proviral DNA contained in infected CD4 T lymphocytes. Plasma separation cards (PSC) collect and preserve a dried specimen, which makes them practical solutions for decentralized sample collection and transport in limited-resource settings. However, physiological variations in hematocrit levels can introduce significant variability in the quality of plasma generated by commercial PSCs and can lead to inaccurate test results and clinical decisions. In addition to hematocrit-dependent sampling, the Roche PSC, a standard for dried plasma collection, is known to induce considerable hemolysis, which further impacts specimen quality, concordance with liquid plasma, and the overall benefit of microsampling. We address these gaps with a patterned dried plasma spot (pDPS) card, which generates plasma with improved hematocrit independence and minimal hemolysis. This study directly compares pDPS cards to the Roche PSC to measure HIV viral load. Analysis of viral load from 75 donors revealed strong agreement in sensitivity, specificity, overall accuracy, and viral load band placement between devices, with quantitative metrics suggesting improved performance for pDPS cards. In reflexive genotyping, remnant dried blood from pDPS cards exhibited greater success than Roche PSC in amplification and sequencing (71% vs. 62%) and detecting drug resistance mutations (63% vs. 42%). Based on this performance, pDPS cards can be versatile across multiple analytical platforms, integrate seamlessly into existing clinical laboratory workflows, and aid clinicians in making accurate treatment decisions.